2022
DOI: 10.1126/sciadv.abo5888
|View full text |Cite
|
Sign up to set email alerts
|

Slamming dynamics of diving and its implications for diving-related injuries

Abstract: In nature, many animals dive into water at high speeds, e.g., humans dive from cliffs, birds plunge, and aquatic animals porpoise and breach. Diving provides opportunities for animals to find prey and escape from predators and is a source of great excitement for humans. However, diving from high platforms can cause severe injuries to a diver. In this study, we demonstrate how similarity in the morphology of diving fronts unifies the slamming force across diving animals and humans. By measuring a time-averaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Beyond informing engineering applications, such forces can prove fatal for human divers if the hydrodynamics are not respected (Pandey et al. 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond informing engineering applications, such forces can prove fatal for human divers if the hydrodynamics are not respected (Pandey et al. 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Other impactors such as aerospace structures (Seddon & Moatamedi 2006) or amphibious autonomous vehicles (Siddall & Kovač 2014;Shi et al 2019b) have benefited from advancements in the area. Beyond informing engineering applications, such forces can prove fatal for human divers if the hydrodynamics are not respected (Pandey et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Competitive divers perform hands first entries such as the rip entry maneuver from heights below 15 m to prevent injury [22]. Consider an Olympic diver performing a dive from the 10 m platform with an impact speed of approximately 16 m/s.…”
Section: Methodsmentioning
confidence: 99%
“…It can be especially helpful to understand what impact forces organisms can withstand and what drop height would cause injury. The impulse force generated at impact for a variety of animals can be predicted by corresponding simplified geometries [22]. Experiments found that birds choose to plunge dive at speeds that keep them within a safe regime [23].…”
Section: Introductionmentioning
confidence: 99%
“…In nature, some animals exhibit diving behaviors with diverse body shapes and surface coverings that have evolved to optimize their interaction with water. 1,2 When an animal dives the shape of the diving front significantly influences the forces encountered; a blunt front tends to increase drag and impact force, whereas a sharp, narrow front can reduce these forces. 3,4 Over evolutionary timescales, these pressures have the potential to alter animal morphology, driving adaptations that minimize resistance and impact during diving.…”
Section: Introductionmentioning
confidence: 99%